PROCESS OPTIMIZATION OF THE MECHANICAL PROPERTIES OF AISI 1020 STEEL QUENCHED USING MAIZE-STOVER ASH POTASH SOLUTION (Nigerian Journal of Technology, 2020)
The process parameter optimization of maize-stover ash potash (MSAP) as a quenching medium for heat treatment of AISI-1020 steel was conducted in this study to improve the mechanical properties of steel after carburization and quenching. The optimization process utilized Taguchi L9(32) orthogonal array method to determine the individual Signal to Noise (S/N) ratio and Analysis of Variance (ANOVA). A multi-response weighted analysis technique was applied to derive combined quality responses of the heat treated test pieces. The result shows that the optimal factor level of MSAP solution strength was achieved at AM1BM1, which offered 57.6 HRC hardness, 39 J toughness and 1971 N/mm2 tensile strength as improved mechanical properties for the heat treated steel.   http://dx.doi.org/10.4314/njt.v39i3.23